The Study and Analysis Grammatical of verbal sentence a fragment of "Zurita" (Leopoldo alas Clarín) - AMEL TAHA AL-ALOOSI (مجلة الآداب, 2020)
This article deals with the study of theories about verbal periphrasis as a grammatical construction; the aim of this point it offers good and valid guidelines to improve the linguistic description. The interest in the subject comes from its importance in the process of language teaching for the students of Spanish and to clarify this type of curriculum of this research we analyzed a literary text. From "Zurita"